The Bleeding Risk in Antithrombotic Therapies: A Narrative Review - Alatri, Adriano; Mazzolai, Lucia (Current Vascular Pharmacology, 2020)
Bleeding represents the most important complication of antithrombotic treatment, including anticoagulant and antiplatelet therapies. A number of scores were proposed to evaluate the risk of bleeding both for anticoagulant and antiplatelet treatment. In the last decade, 5 bleeding risk scores were published for use in atrial fibrillation patients, and 3 scores for patients receiving anticoagulants for venous thromboembolism therapy or prophylaxis. In addition, 3 scores were recently developed to assess inhospital or short-term bleeding risk in patients receiving antiplatelet therapy after Acute Coronary Syndrome (ACS) and Percutaneous Coronary Intervention (PCI). Furthermore, 3 additional scores have focused on long-term bleeding in outpatients receiving dual antiplatelet therapy after PCI. The aim of this review is to consider the evidence on bleeding scores.
Keywords: Bleeding